Postliver Transplantation Rhino-Orbital Mucormycosis, an Unexpected Cause of a Downhill Course - Swapnali Sabhapandit; Mithun Sharma; Anuradha Sekaran; Balachandran Menon; Anand Kulkarni; Soumya TR; Padaki Nagaraja Rao; Duvurr Nageshwar Reddy (Case Reports in Hepatology)
The COVID-19 pandemic has impacted transplantation worldwide in a major way with infections and post-COVID-19 complications contributing to increased mortality and morbidity. We present a case of a 42-year-old lady who developed rhino-orbital mucormycosis in a postliver transplantation period. The initial presentation of the patient was very subtle. She never had overt COVID-19 infection before surgery and in the recovery period. Though cases of mucormycosis in the wound site have been reported, this would be one of the rare cases of rhino-orbital mucormycosis postliver transplantation. This infection leads to a rapid downhill course and the death of the patient. Atypical infections and presentations need to be monitored in postliver transplantation patients who are getting operated on during this pandemic, and a high level of clinical suspicion is required to pick up these cases at an early stage.